ILCA 1990: Annual report and programme highlights - International Livestock Centre for Africa (International Livestock Centre for Africa, 1991)
Presents ILCA's achievements in 1990 in a popular, easily read style. The Cattle Milk and Meat Thrust highlight focusses on peri-urban dairying, and particularly the work of collaborative programme with KARI. The highlights of the Small Ruminant Meat and Milk Thrust are linked by their focus on interactions between animals and other components of the agricultural system. The Animal Traction Thrust highlights focus on two themes central to the Thrust's work: feeding and alternative sources of draft power. Highlights of the Animal Feed Resource Thrust focus on in vitro culture work with multipurpose tree germplasm and studies of breeding systems of African clovers and Sesbania species. As the highlights show, the work of the Trypanotolerance Thrust in collaboration with NARS & ILRAD is opening up possibilities for selection of animal that show both tolerance and productivity. The highlights of the Livestock Policy and Resource Use Thrust are two multi-country studies, one on land tenure and alley farming and the other on price policies. The highlights of the Training and Information Department is the topic of integration of long-term individual trainees with the centre's research programme and integration of several bibliographic databases to increase the effectiveness of the centre's information services.